Cholangiocarcinoma associated with limbic encephalitis and early cerebral abnormalities detected by 2-deoxy-2-[fluorine-18]fluoro-d-glucose integrated with computed tomography-positron emission tomography: a case report. (December 2016) - Schmidt, Sergio; Schmidt, Juliana; Tolentino, Julio; Ferreira, Carlos; de Almeida, Sergio; Alvarenga, Regina; Simoes, Eunice; Schmidt, Guilherme; Canedo, Nathalie; Chimelli, Leila
Abstract Background Limbic encephalitis was originally described as a rare clinical neuropathological entity involving seizures and neuropsychological disturbances. In this report, we describe cerebral patterns visualized by positron emission tomography in a patient with limbic encephalitis and cholangiocarcinoma. To our knowledge, there is no other description in the literature of cerebral positron emission tomography findings in the setting of limbic encephalitis and subsequent diagnosis of cholangiocarcinoma. Case presentation We describe a case of a 77-year-old Caucasian man who exhibited persistent cognitive changes 2 years before his death. A cerebral scan obtained at that time by 2-deoxy-2-[fluorine-18]fluoro- d - glucose integrated with computed tomography-positron emission tomography showed low radiotracer uptake in the frontal and temporal lobes. Cerebrospinal fluid analysis indicated the presence of voltage-gated potassium channel antibodies. Three months before the patient's death, a lymph node biopsy indicated a cholangiocarcinoma, and a new cerebral scan obtained by 2-deoxy-2-[fluorine-18]fluoro-d -glucose integrated with computed tomography-positron emission tomography showed an increment in the severity of metabolic deficit in the frontal and parietal lobes, as well as hypometabolism involving the temporal lobes. Two months before the patient's death, cerebral metastases were detected on a contrast-enhanced computed tomographic scan. Postmortem examination revealed a cholangiocarcinoma with multiple metastases including the lungs and lymph nodes. The patient's brain weighed 1300 g, and mild cortical atrophy, ex vacuo dilation of the ventricles, and mild focal thickening of the cerebellar leptomeninges, which were infiltrated by neoplastic epithelial cells, were observed. Conclusions These findings support the need for continued vigilance in malignancy surveillance in patients with limbic encephalitis and early cerebral positron emission tomographic scan abnormalities. The difficulty in early diagnosis of small tumors, such as a cholangiocarcinoma, is discussed in the context of the clinical utility of early cerebral hypometabolism detected by 2-deoxy-2-[fluorine-18]fluoro-d -glucose integrated with computed tomography-positron emission tomography in patients with rapidly progressive dementia.